Histopathology and cytopathology of white spot syndrome virus (WSSV) in cultured Penaeus monodon from peninsular Malaysia with emphasis on pathogenesis and the mechanism of white spot formation - Wang, Y.G.; Hassan, M.D.; Shariff, M.; Zamri, S.M.; Chen, X. (Inter-Research, 1999)
Since 1994, white spot syndrome virus (WSSV) has been detected in cultured shrimp Penaeus monodon in Peninsular Malaysia. The gross signs, target organs and histo-cytopathology for the viral infection were studied and it was found to infect most organs and tissues including oocytes, but not hepatopancreatocytes and epithelial cells of the midgut, which were regarded as refractory tissues. Based on a time-sequence of ultrastructural cytopathology, 4 cytopathic profiles and 6 phases of viral morphogenesis were described. The virions were elliptical to short rods with trilamilar envelopes that measured 305 ± 30 x 127 ± 11 nm. Viral nucleosomes were often present singly in infected nuclei and were associated with the early stages of viral replication. The structure of WSSV pathognomonic white, cuticular lesions was examined at the microscopic and ultrastructural levels and the mechanism of their formation appeared to be related to the disruption of exudate transfer from epithelial cells to the cuticle via cuticular pore canals.